The 5' end of coronavirus minus-strand RNAs contains a short poly(U) tract. - Hofmann, M A (1991)
A radiolabeled oligodeoxynucleotide primer that anneals near the common 5' end of bovine coronavirus minus-strand RNAs was extended with reverse transcriptase, and a major product suggesting poly(U) tracts of 8 to 20 nucleotides was found. The extended primer molecules were ligated head to tail, amplified by the polymerase chain reaction, cloned, and sequenced, and poly(U) tracts of 9 to 26 nucleotides were found. Poly(A) tails of 100 to 130 nucleotides on the 3' end of coronavirus plus-strand mRNAs and genome must, therefore, be generated by a mechanism that uses only a short poly(U) template. This pattern contrasts with that of other cytoplasmic, polyadenylated, plus-strand animal RNA viruses which utilize a full-length poly(U) template for poly(A) synthesis.